The fibronectin III-1 domain activates a PI3-Kinase/Akt signaling pathway leading to αvβ5 integrin activation and TRAIL resistance in human lung cancer cells. Issue 1 (December 2016) - Cho, Christina; Horzempa, Carol; Jones, David; McKeown-Longo, Paula
Abstract Background Fibronectin is a mechanically sensitive protein which is organized in the extracellular matrix as a network of interacting fibrils. The lung tumor stroma is enriched for fibronectin which is thought to contribute to metastasis and drug resistance. Fibronectin is an elastic, multi-modular protein made up of individually folded domains, some of which can stretch in response to increased mechanical tension. Very little is known about the relationship of fibronectin's unfolded domains to lung cancer resistance to chemotherapy. In the present study, we evaluated the impact of unfolding the first Type III domain of fibronectin (FnIII-1c) on TNF-related apoptosis inducing ligand (TRAIL) resistance. Methods NCI-H460 non-small cell lung cancer cells were treated with FnIII-1c then assessed for TRAIL-induced apoptosis. Subsequent analysis of FnIII-1c-mediated signaling pathways was also completed. Human non-small cell lung cancer tissue sections were assessed for the expression of vitronectin by immunohistochemistry. Results FnIII-1c inhibited TRAIL-induced activation of caspase 8 and subsequent apoptosis in NCI-H460 lung cancer cells. FnIII-1c treatment was associated with the activation of the phosphatidylinositol-3-kinase/alpha serine/threonine kinase (PI3K/Akt) pathway and the αvβ5 integrin receptor for vitronectin, both of which were required for TRAIL resistance. Immunohistochemical staining of sections from non-small cell lung cancers showed that vitronectin was localized around blood vessels and in the tumor-stroma interface. Conclusions Unfolding of Type III domains within the fibronectin matrix may promote TRAIL resistance through the activation of a PI3K/Akt/αvβ5 signaling axis and point to a novel mechanism by which changes in secondary structure of fibronectin contribute to cancer cell resistance to apoptosis.